Magmatic tempo of Earth's youngest exposed plutons as revealed by detrital zircon U-Pb geochronology. - Ito, H.; Spencer, Christopher; Danišík, M.; Hoiland, C. (Nature Publishing Group, 2017)
Plutons are formed by protracted crystallization of magma bodies several kilometers deep within the crust. The temporal frequency (i.e. episodicity or 'tempo') of pluton formation is often poorly constrained as timescales of pluton formation are largely variable and may be difficult to resolve by traditional dating methods. The Hida Mountain Range of central Japan hosts the youngest exposed plutons on Earth and provides a unique opportunity to assess the temporal and spatial characteristics of pluton emplacement at high temporal resolution. Here we apply U-Pb geochronology to zircon from the Quaternary Kurobegawa Granite and Takidani Granodiorite in the Hida Mountain Range, and from modern river sediments whose fluvial catchments include these plutons in order to reconstruct their formation. The U-Pb data demonstrate that the Kurobegawa pluton experienced two magmatic pulses at ~2.3?Ma and ~0.9?Ma; whereas, to the south, the Takidani pluton experienced only one magmatic pulse at ~1.6?Ma. These data imply that each of these magmatic systems were both spatially and temporally distinct. The apparent ~0.7?Myr age gap between each of the three magmatic pulses potentially constrains the recharge duration of a single pluton within a larger arc plutonic complex.